(untitled) (Fiep Bulletin - online, 2012)
At the complexity age, the search for Peace has turned out to constitute action in every sector of humanactivities. Physical Education and Sports ended up by becoming considered instruments of Peace for therecognition of people’s rights to physical activities. This right has been expressed in many important internationaldocuments, such as the International Charter of Physical Education (UNESCO), the Charter of Children’s Rightsin Sports (Panathlon) and FIEP-2000 World Manifesto of Physical Education.In addition of UNESCO’s effective work, UNO is also committed with the relationships between Sportsand Peace. In order to do so, it has strengthened the ties between Sports and Health, Education, SustainableDevelopment, Cooperation and other aspects, in a program called “Millennium Development Goals” (MDGs).As a conclusion it can be stated that there is consensus about the usage of Physical Education andSports in favor of the Culture of Peace as a right granted to everyone. So, the emphasis should be on thecollective-oriented idea, without and kind of discrimination.